The Role of Complex Trauma and Attachment Patterns in Intimate Partner Violence - Speranza, Anna Maria; Farina, Benedetto; Bossa, Caterina; Fortunato, Alexandro; Maggiora Vergano, Carola; Palmiero, Luigia; Quintigliano, Maria; Liotti, Marianna (Frontiers in Psychology, 2022)
Objective Even if the relationship between adverse childhood experiences and intimate partner violence (IPV) has already been established, there are no sufficient studies examining the relationships between these factors and attachment representations, specifically attachment disorganization. Thus, this study aimed to explore, in a sample of women who experienced IPV (a) the presence of interpersonal adversities during childhood, and (b) attachment representations, with a particular focus on disorganization. Methods Women’s representations of attachment experiences were investigated through the Adult Attachment Interview, while the presence of various forms of interpersonal adversities during childhood was assessed using the Complex Trauma Questionnaire. The results of the IPV group (n = 98) were compared with those of women with no history of IPV (control group, n = 81). Results Women in the IPV group showed higher values of multiple forms of adverse experiences within their caregiving system. They presented significantly higher rates of disorganized states of mind regarding attachment, indicative of a lack of resolution regarding traumatic experiences, and of disorganized working models resulting from complex trauma. Our results highlighted that, more than the presence of traumatic experiences, it is their irresolution – reflected in the disorganized states of mind regarding attachment at the Adult Attachment Interview – to be a significant predictor of IPV. Conclusion These results suggest underline the significance of offering a trauma- and attachment-informed therapy to those who experience IPV. Such results could help both clinicians and researchers in formulating clearer guidelines for IPV interventions.